NEW FUNCTION
Function Expression :
\[f(x)=\frac{(2x^2-3x+4
)}{x-1} \]
Domain
\[\left]-\infty, 1\right[ \cup \left]1, \infty\right[ \]
Limits
\[\lim_{x \rightarrow-\infty}f(x) = -\infty \]
\[\lim_{x \overset{<}{\rightarrow1} }f(x) = -\infty \]
\[\lim_{x \overset{>}{\rightarrow1} }f(x) = +\infty \]
\[\lim_{x \rightarrow+\infty}f(x) = +\infty \]
\[ \]
Derivate
\[f^{\,\prime}(x)=\frac{4 x - 3}{x - 1} - \frac{2 x^{2} - 3 x + 4}{\left(x - 1\right)^{2}} \]
\[f^{\,\prime}(x)=\frac{2 x^{2} - 4 x - 1}{x^{2} - 2 x + 1} \]
\[ \]
Integral
\[F(x) = x^{2} - x + 3 \log{\left(x - 1 \right)} \]
Sign Table
Variation Table
Plot
Elapsed Time: 0.0282 seconds